Power system with multi-type FACTS devices states estimation based on predictor-corrector interior point algorithm - Rakpenthai C. (2014)
This paper addresses a state estimation problem of power systems incorporating various flexible alternating current transmission system (FACTS) devices. Static var compensators, thyristor controlled series compensators, and unified power flow controllers are considered since they represent various kinds of FACTS devices. By considering constraints of system buses and devices, the estimation problem can be formulated as a nonlinear optimization with constraints. An algorithm based on predictor-corrector interior point is applied to solve the problem. The IEEE 14- and 118-bus systems modified by incorporating FACTS devices are used as test systems to verify and demonstrate the effectiveness of the proposed algorithm. Numerical results indicate that the proposed algorithm performs better than the primal dual interior point based method even the presence of bad measurement data. © 2008 Elsevier Ltd. All rights reserved.